2017
DOI: 10.3390/biom7040077
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Conservation of the Components in the TOR Signaling Pathways

Abstract: Target of rapamycin (TOR) is an evolutionarily conserved protein kinase that controls multiple cellular processes upon various intracellular and extracellular stimuli. Since its first discovery, extensive studies have been conducted both in yeast and animal species including humans. Those studies have revealed that TOR forms two structurally and physiologically distinct protein complexes; TOR complex 1 (TORC1) is ubiquitous among eukaryotes including animals, yeast, protozoa, and plants, while TOR complex 2 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 76 publications
3
89
0
10
Order By: Relevance
“…However, the model proposed was that, under appropriate stress conditions (including hypotonic shock and sphingolipid depletion), Slm1/2 dissociate from eisosomes, bind Ypk1, and deliver this substrate to the TORC2 compartment (Berchtold et al 2012;Niles et al 2012). On the other hand, equally compelling data demonstrate that it is the CRIM element present in Avo1 and its orthologs in fission yeast (Sin1) and mammalian cells (mSIN1) that binds and presents substrates to the catalytic center in TORC2 (Liao and Chen 2012;Tatebe and Shiozaki 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the model proposed was that, under appropriate stress conditions (including hypotonic shock and sphingolipid depletion), Slm1/2 dissociate from eisosomes, bind Ypk1, and deliver this substrate to the TORC2 compartment (Berchtold et al 2012;Niles et al 2012). On the other hand, equally compelling data demonstrate that it is the CRIM element present in Avo1 and its orthologs in fission yeast (Sin1) and mammalian cells (mSIN1) that binds and presents substrates to the catalytic center in TORC2 (Liao and Chen 2012;Tatebe and Shiozaki 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In most land plants, chlorophytes and rhodophytes, no RICTOR ortholog has been found suggesting that only TORC1 is conserved (Shi, Wu, & Sheen, 2018;Tatebe & Shiozaki, 2017;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We further explored this relationship between the requirement for SKN-1 and MOM-2 by testing other candidate genes implicated in endoderm development [6870]. We found that loss of RICT-1, the C. elegans orthologue of the human RICTOR (Rapamycin-insensitive companion of mTOR; [71]), a component of the TORC2 complex, which has been shown to antagonize SKN-1 function [68], results in opposite effects on skn-1(-) and mom-2(-) mutants (Fig. 8A).…”
Section: Resultsmentioning
confidence: 99%